Biorthogonal Wavelet on a Logarithm Curve ℂ - Xiaohui Zhou; Gang Wang (Journal of Mathematics)
According to the length-preserving projection and Euler discretization method, biorthogonal wavelet function on a smooth curve C is constructed in this paper, such as a logarithm curve. The properties of biorthogonal wavelet filters on a smooth curve C are discussed, such as induced refinable equation and symmetry. Moreover, an example is given for discussing the biorthogonal scaling function and its dual on a logarithm curve C. Finally, a numerical application is given for dealing with financial data.